1985
DOI: 10.1159/000226049
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma von Willebrand Factor Levels and Arterial Occlusive Complications Associated with Cisplatin-Based Chemotherapy

Abstract: Factor-VIII-related von Willebrand factor (vWF) multimers are synthesized by endothelial cells, and plasma vWF antigen levels are elevated in some disorders associated with endothelial cell perturbation. We studied 13 patients during cisplatin-basedcombination chemotherapy for squamous cell carcinoma of the head and neck, esophagus, or lung. Before therapy, 3 of the patients had vWF antigen levels that were ≥400% of normal; and further elevations occurred during chemotherapy. Two of these patients had cerebrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
9

Year Published

1989
1989
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(88 citation statements)
references
References 9 publications
0
77
0
9
Order By: Relevance
“…Although it may arise from the endothelium, lack of correlation with endothelial marker vWf 22 implies it also arises from other tissues. Raised vWf in prostate cancer (as in many cancers) is an established finding and may reflect endothelial disturbance, which in our study can not due to cytotoxic chemotherapy, 23 as the latter is an exclusion criterion. Therefore raised vWf may reflect a non-specific response to the tumour, or perhaps secretion from para-tumoric endothelial cells, although lack of correlation between vWf and VEGF implies such a disturbance is unrelated to angiogenesis.…”
Section: Discussionmentioning
confidence: 73%
“…Although it may arise from the endothelium, lack of correlation with endothelial marker vWf 22 implies it also arises from other tissues. Raised vWf in prostate cancer (as in many cancers) is an established finding and may reflect endothelial disturbance, which in our study can not due to cytotoxic chemotherapy, 23 as the latter is an exclusion criterion. Therefore raised vWf may reflect a non-specific response to the tumour, or perhaps secretion from para-tumoric endothelial cells, although lack of correlation between vWf and VEGF implies such a disturbance is unrelated to angiogenesis.…”
Section: Discussionmentioning
confidence: 73%
“…Such tumors may secrete abnormally glycosylated mucins and mucin fragments into the blood stream, which are associated with coagulopathies (22). As Trousseau's syndrome was originally reported to be associated with mucin-producing adenocarcinomas (23), some early studies suggested that secreted mucin might act as a procoagulant for hypercoagulopathy (5 (18), which are also considered to be associated with endothelial injuries (10,24,25), although the precise mechanism remains unclear. Indeed, protein C can be modified by proteolytic enzymes released by endothelial injuries (26).…”
Section: Case Reportmentioning
confidence: 99%
“…The mechanisms of cisplatin-induced vascular events remain unknown and may be mediated by endothelial dysfunction, toxicity, vasospasm, autonomic dysfunction, vasculitis and stimulation of fibroblasts, or abnormalities in the coagulation cascade directly produced or induced by chemotherapy 3,4 . High-dose dexamethasone administered as an antiemetic with cisplatin may be an independent prognostic factor for development of a vascular event 5 .…”
Section: Discussionmentioning
confidence: 99%